Pengembangan Pola Rekrutmen Guru Di Pondok Pesantren Modern Imam Syuhodo Muhammadiyah Cabang Blimbing Daerah Sukoharjo - Handayani, Nurhakimah Siwi, Prof. Bambang Sumardjoko, M,Pd, Dra. Titik Asmawati, SE, M.Si (2015)
The Purpose of this study, to describe patterns of teacher recruitment which include, (1) the planning needs of teachers in Pondok Pesantren Modern Imam Syuhodo, (2) the implementation of the recruitment of teachers in Pondok Pesantren Modern Imam Syuhodo, (3) the responses and expectations components of school in the development pattern recruitment of teachers in Pondok Pesantren Modern Imam Syuhodo. This study is a qualitative study with ethnographic approach. Research conducted at the Pondok Pesantren Modern Imam Syuhodo. The main data was obtained from the director of the cottage, the principal unit of education, teacher, Branch Chairman of Muhammadiyah Blimbing. Data were collected by interview, observation and documentation. Data were analyzed through data collection, data reduction, data presentation and conclusion. The validity of the data using triangulation of data sources. The results showed: (1) planning needs to consider the needs of teachers and availability of teachers at the school, teaching hours per week according to subject existing teaching hours and study groups, (2) the implementation of the recruitment of teachers to implement internal policies. Recruitment implemented educational unit, the authority to decide the hands of the director, the board of religious scholars and foundations. Source of recruitment of teachers of general application, preferably from alumnis and cadres Persyarikatan. (3) the responses and expectations of the school component in the development of teacher recruitment patterns through the optimization of existing rules, religious test and microteaching to determine the ability of the start of prospective teachers.